2017
DOI: 10.1158/1541-7786.mcr-16-0372
|View full text |Cite
|
Sign up to set email alerts
|

The Microtubule Network and Cell Death Are Regulated by an miR-34a/Stathmin 1/βIII-Tubulin Axis

Abstract: MicroRNA-34a (miR-34a) is a master regulator of signaling networks that maintain normal physiology and disease and is currently in development as a miRNA-based therapy for cancer. Prior studies have reported low miR-34a expression in osteosarcoma (OS); however, the molecular mechanisms underlying miR-34a activity in OS are not well defined. Therefore, this study evaluated the role of miR-34a in regulating signal transduction pathways that influence cell death in OS. Levels of miR-34a were attenuated in human O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…In cell cycle progression, STMN1 integrates different signals to regulate microtubule polymerization and depolymerization to adapt to different stages of the cell cycle 55 . For example, STMN1 acts as an oncogene that promotes the proliferation of osteosarcoma cells 56 . STMN1 has been found to be an important tubulin that inhibits the stability of microtubules (MT), thereby enhancing tumor cell proliferation, invasion and metastasis 57 .…”
Section: Discussionmentioning
confidence: 99%
“…In cell cycle progression, STMN1 integrates different signals to regulate microtubule polymerization and depolymerization to adapt to different stages of the cell cycle 55 . For example, STMN1 acts as an oncogene that promotes the proliferation of osteosarcoma cells 56 . STMN1 has been found to be an important tubulin that inhibits the stability of microtubules (MT), thereby enhancing tumor cell proliferation, invasion and metastasis 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Significant modules were identified to be correlated with osteosarcoma. For the purple module, which was mainly related with microtubule bundle formation, drug metabolism-cytochrome P450, and IL-17 signaling pathway and was identified to be negatively correlated with the trait of osteosarcoma, while being positively correlated with the trait of metastasis in osteosarcoma, previous studies have reported that increase of microtubule destabilization was related with G1/G2 phase cell cycle arrest and apoptosis, and microtubule inhibitors could trigger autophagy and cell death in osteosarcoma cell line [10]. Besides, IL-17A/IL-17RA interaction promoted metastasis of osteosarcoma cells [11].…”
Section: Discussionmentioning
confidence: 99%
“…Stathmin-1: Stathmin-1 is a microtubule-destabilizing cytosolic phosphoprotein that plays an important role in tumor cell proliferation and migration and may be regulated by miR-34a[30,31], miR-223[32] and miR-193b[33]. It is associated with cancer metastasis and poor prognosis in osteosarcoma[31,34], prostate cancer[35,36], head and neck squamous cell carcinoma[37], hepatocellular carcinoma[32], colorectal cancer[33,38], gallbladder carcinoma[39] and non-small-cell lung cancer[40]. In esophageal squamous cell carcinoma (ESCC), stathmin-1 is also vital for ESCC invasiveness and predicts a poor prognosis[41].…”
Section: Exosome and Esophageal Cancer Tumorigenesismentioning
confidence: 99%